2013
DOI: 10.1371/journal.ppat.1003118
|View full text |Cite|
|
Sign up to set email alerts
|

IRF-3, IRF-5, and IRF-7 Coordinately Regulate the Type I IFN Response in Myeloid Dendritic Cells Downstream of MAVS Signaling

Abstract: Although the transcription factors IRF-3 and IRF-7 are considered master regulators of type I interferon (IFN) induction and IFN stimulated gene (ISG) expression, Irf3−/−×Irf7−/− double knockout (DKO) myeloid dendritic cells (mDC) produce relatively normal levels of IFN-β after viral infection. We generated Irf3−/−×Irf5−/−×Irf7−/− triple knockout (TKO) mice to test whether IRF-5 was the source of the residual induction of IFN-β and ISGs in mDCs. In pathogenesis studies with two unrelated positive-sense RNA vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
266
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(287 citation statements)
references
References 86 publications
(152 reference statements)
20
266
0
1
Order By: Relevance
“…The choroid plexuses are located within the ventricles and have a rich blood supply, located between the blood-brain and blood-ventricle barriers (1). The presence of these tissues within the brain prevents evaluation of virus spread among neurons and glia using methods such as titration of virus from homogenized tissue or qPCR for viral genes (14,43,49) because such methods cannot differentiate between virus load in CNS and non-CNS tissues. The presence of these structures also prevents conclusions regarding CNS innate immunity following peripheral infections, because peripheral infections can pass through both the brain's vasculature and lymphatics, and these structures can mount innate immune responses (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choroid plexuses are located within the ventricles and have a rich blood supply, located between the blood-brain and blood-ventricle barriers (1). The presence of these tissues within the brain prevents evaluation of virus spread among neurons and glia using methods such as titration of virus from homogenized tissue or qPCR for viral genes (14,43,49) because such methods cannot differentiate between virus load in CNS and non-CNS tissues. The presence of these structures also prevents conclusions regarding CNS innate immunity following peripheral infections, because peripheral infections can pass through both the brain's vasculature and lymphatics, and these structures can mount innate immune responses (1).…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate the induction of the type I IFN response, the expression of several known ISGs-Rsad2, Cxcl10, and Oas1α-was assayed (43). Compared with PBS injection, DIPs led to an induction in Rsad2 (Fig.…”
Section: Evaluation Of the Response Within Microglia Following Infectmentioning
confidence: 99%
“…A pharmacological study indicated that MV-derived IFN- expression partially depended on NF-B (Takaki et al, 2014). A recent study using West Nile virus showed that IRF3/IRF7 and IRF5 coordinately regulate the type I IFN response in DCs (Lazear et al, 2013). For MV, IRF5 might be a transcription factor for MAVS-dependent and IRF3/IRF7-independent type I IFN induction in BMDCs (Figure 2).…”
Section: Studies In Mice With Targeted Gene Deletions Provide Insightmentioning
confidence: 95%
“…In addition to IRF3/7, accumulating evidence suggests that IRF1, IRF5, and IRF8 trigger IFN responses in cell-specific fashions (5)(6)(7)(8). IRF1 is the founder member of the IRF family and initially was identified as a positive regulator directly binding to type I IFN gene promoters (9).…”
mentioning
confidence: 99%